2021
DOI: 10.1186/s12984-020-00802-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and motor deficits contribute to longer braking time in stroke

Abstract: Background Braking is a critical determinant of safe driving that depends on the integrity of cognitive and motor processes. Following stroke, both cognitive and motor capabilities are impaired to varying degrees. The current study examines the combined impact of cognitive and motor impairments on braking time in chronic stroke. Methods Twenty stroke survivors and 20 aged-matched healthy controls performed cognitive, motor, and simulator driving as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Case control studies comparing stroke patients with healthy age-matched controls using driving simulators found that stroke patients had difficulty maintaining their lanes, with ischaemic stroke patients having difficulty maintaining their speed (Hird et al., 2018). Braking time was 16% longer in the stroke patient group compared with control groups (Lodha et al., 2021). Cognitive assessments showed stroke patients took significantly longer to complete tasks relating to divided attention and selective attention when compared with controls (Lodha et al., 2021).…”
Section: Community Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Case control studies comparing stroke patients with healthy age-matched controls using driving simulators found that stroke patients had difficulty maintaining their lanes, with ischaemic stroke patients having difficulty maintaining their speed (Hird et al., 2018). Braking time was 16% longer in the stroke patient group compared with control groups (Lodha et al., 2021). Cognitive assessments showed stroke patients took significantly longer to complete tasks relating to divided attention and selective attention when compared with controls (Lodha et al., 2021).…”
Section: Community Participationmentioning
confidence: 99%
“…Braking time was 16% longer in the stroke patient group compared with control groups (Lodha et al, 2021). Cognitive assessments showed stroke patients took significantly longer to complete tasks relating to divided attention and selective attention when compared with controls (Lodha et al, 2021). A Cochrane review concluded there was insufficient evidence to determine whether any rehabilitation intervention improved patients' driving abilities after a stroke (George et al, 2014).…”
Section: Driving Advicementioning
confidence: 99%
“…For example, post-stroke impairments in upper limb force control contribute to steering dysfunction ( 6 ). Likewise, stroke-related impairments in lower limb motor accuracy are linked to slower braking response ( 7 ). Unsurprisingly, therefore, the severity of motor impairments after stroke predicts an individual's likelihood of self-regulating driving after stroke and returning to driving 6 months post-stroke ( 2 , 4 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Well-timed braking response requires cognitive processing to recognize changes in the driving environment and motor capabilities for fast and accurate pedal manipulations. Accordingly, decline in cognitive speed of processing after stroke has been shown to delay the braking times ( 7 ). Although there is evidence that reduced muscle strength compromises braking speed in older adults ( 11 , 12 ), our recent findings suggest that braking performance in stroke survivors relates to reduced motor control but not to muscle strength ( 7 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation